Role of Structured Counseling and Health Education in Enhancing Awareness and Self-care among Type 2 Diabetes Mellitus Patients in a Tertiary Care Setting of Rajasthan, India - Mathur, Navgeet; Shrimali, Lalit; Kerasiya, Kalpesh; Mathur, Medha; Basu, Abhijit (Indian Journal of Community Health, 2025)
Background: Control of risk factors by lifestyle and dietary modification is an essential part of Diabetes mellitus Type 2 management. The counseling of patients is needed to impart knowledge and to create awareness regarding self-care in diabetes mellitus cases. Health education using awareness material for the diabetes patients enhances self-care and in turn results in glycemic control of diabetes mellitus. Objectives: The study was designed to assess pre- and post-effect of counseling and education material distribution in DM Type 2 patients. Methodology: The cross-sectional study was conducted on 210 indoor diabetic patients. Pre and post-intervention evaluation was done by a questionnaire. Intervention was done in form of counseling, online and offline education material distribution. Results: There was an improvement in retention of knowledge and patient satisfaction on post-intervention evaluation. On pre intervention evaluation only 29% patients were able to remember sufficient amount of information given by the doctor and only 52% patients were either satisfied or strongly satisfied. After intervention 98.5% patients were able to remember sufficient amount of information given by the doctor and 100% patients were either satisfied or strongly satisfied. Conclusion: Distribution of online and offline education material with counselling can improve retention of knowledge and patient satisfaction. Education material distribution with counselling should be part of the health care system.